Self-Reported vs Measured Physical Fitness in Older Women - Kasović M (Dove Medical Press, 2020)
Mario Kasović,1,2 Lovro Štefan,1 Martin Zvonar2 1Faculty of Kinesiology, Department of General and Applied Kinesiology, University of Zagreb, Zagreb, Croatia; 2Faculty of Sports Studies, Department of Kinesiology, Masaryk University, Brno, Czech RepublicCorrespondence: Lovro ŠtefanFaculty of Kinesiology, University of Zagreb, Horvaćanski Zavoj 15, Zagreb, CroatiaTel +385 98-9177-060Email lovro.stefan1510@gmail.comPurpose: The main purpose of the study was to determine the level of correlation between self-reported and measured physical fitness.Patients and Methods: In this cross-sectional study, we recruited 120 older women aged ≥ 60 years. Self-reported physical fitness was assessed on a scale from 1 to 10, where higher score indicated better physical fitness perception. Objective measure included seven physical fitness tests: 1) waist circumference, 2) chair stand in 30 sec, 3) arm curl in 30 sec, 4) 2-min step test, 5) chair sit-and-reach test, 6) back scratch test and 7) 8-feet up-and-go test. Correlation between the two measures was analyzed by using Spearman coefficient (p≤ 0.05).Results: In the whole sample, self-reported physical fitness was associated with chair stand in 30 sec (r=0.39, p< 0.001), arm curl in 30 sec (r=0.54, p< 0.001), 2-min step test (r=0.43, p< 0.001), chair sit-and-reach test (r=0.39, p< 0.001), back scratch test (r=0.36, p< 0.001) and 8-feet up-and-go test (r=− 0.29, p< 0.001). No significant correlation between self-reported physical fitness and waist circumference was found (r=0.03, p=0.786). Overall physical fitness (sum of all physical fitness z-scores) was strongly correlated with self-reported physical fitness (r=0.63, p< 0.001).Conclusion: This study shows that self-reported measure of physical fitness is moderately correlated to objectively measured physical fitness in relatively healthy older women.Keywords: performance, aging, perception, correlation, variance